การใช้และความต้องการใช้สารสนเทศอิเล็กทรอนิกส์ของอาจารย์มหาวิทยาลัยเชียงใหม่ - ตะวัน สุริยะวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Research title, “Use and Needs of Electronic Information by Faculty at Chiang Mai University”, was aimed at studying the use and needs of electronic information of Chiang Mai University lecturers, along with problems on using electronic information and the management for electronic information service of Chiang Mai University main library. This study was a survey research; data were collected from using questionnaires. Samples of this study were 346 lecturers of Chiang Mai University of the second semester, year 2013. Statistics used in this study were frequency, percentage, mean and standard deviation. Results from the study showed that most of the lecturers were female, age 30-39 years old, holding a doctoral degree, they have academic positions as lecturers under the health science programs. They have experienced more than 6 years in using computer, internet and the database of Chiang Mai University main library. They had high skills in using computer and internet. In addition, their skill in using database of the main library was in a medium level. Most of them search for information from 9.00-12.00 a.m. and used internet for searching information more than using database of the main library. In terms of electronic information using, it was found that most of the lecturers used laptop and desktop as devices for seeking for information respectively. They also accessed in electronic information and database of the main library from faculties or departments. In terms of the purposes for using electronic information, they used it for teaching and doing researches. The reasons that they used electronic information were that searching from electronic information was faster than publication. They used electronic information every day, more than 3 hours per day. Surveyed from database of the main library, most of the lecturers used journals more than books and local databases. Problems on using electronic information were that they did not know how to evaluate quality documents, which sources to start seeking for information from and the difficulties in using main library website. In terms of needs for electronic information services from the main library, lectures agreed that the most service provided close to their expectations were main library staffs were able to gain trust from users, fast speed of wireless and internet which coving all of using areas, and modern database, respectively. However, main library should be improved on the stability of network system, adding more specific subjects’ database, along with training for developing skills for accessing electronic information.